REQUIRED AND SUFFICIENT LEVEL OF GSM BASE STATIONS ELECTROMAGNETIC RADIATION POWER - V. I. Mordachev; A. S. Svistunov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Estimations of levels of the equivalent isotropic radiated power in frequency channels of GSM 900/1800 base stations (BS) which are required and sufficient for the effective utilization of radio-frequency resource allocated to the GSM network, are resulted. Analysis is performed for various BS antenna heights, various population density, various levels of real sensitivity of BS radio reception, various cluster dimension of GSM network frequency planning and different specific traffic intensity.